Transformation of Business Licensing through a Single Submission System on Public Service Efficiency: A Case Study of the Indonesia National Single Window Agency (LNSW) - Rizha Febriyanti; Ranti, Benny; Shihab, Muhammad Rifki; Wicaksana, I Gusti Ngurah Adi; Mekkawati, Handini; Salbari, Faris; Diarto, Nur (AI Society & STMIK Indonesia, 2024)
The Indonesia National Single Window (LNSW) Agency developed a single submission system, namely the Indonesia National Single Window (SINSW) System, as a one-stop submission facility. Before the development of SINSW, the process of applying for business permits in Indonesia was complicated and time-consuming. This is because stakeholders have to process permits directly with various relevant ministries or institutions, causing data repetition and cost and time inefficiencies in the export, import and logistics processes. This research aims to analyze the transformation of LNSW into a one-stop business licensing and management agency through the implementation of SINSW and its impact on the efficiency of public services in exports, imports and logistics in Indonesia. This research also compares the implementation of the National Single Window (NSW) in Korea, Singapore, and Japan. The results of the research are recommendations for improving the efficiency of LNSW services in the future through the adoption of artificial intelligence (AI) via chatbots to handle complaints of slow responses for service users.